Workplace-Related Interpersonal Group Psychotherapy to Improve Life at Work in Individuals With Major Depressive Disorders: A Randomized Interventional Pilot Study - Niedermoser, Daryl Wayne; Kalak, Nadeem; Kiyhankhadiv, Anna; Brand, Serge; Walter, Corinna; Schweinfurth, Nina; Lang, Undine E. (Frontiers in Psychiatry, 2020)
Objectives: Individuals suffering from major depressive disorder (MDD) often report workplace-related stress as the major cause of their disorder. Accordingly, workplace-related stress was established as a fifth psychosocial problem area of Interpersonal Psychotherapy (workplace-related Interpersonal Psychotherapy, W-IPT). The aim of the study was to investigate the influence of W-IPT on depressive symptoms and on workplace-related issues in individuals with MDD, compared to a treatment as usual (TAU) condition. Methods: A total of 27 individuals with MDD (mean age = 43 years, 48% males) were randomly assigned either to eight weekly group sessions of W-IPT or to the TAU condition. At baseline, eight weeks later at the end of the intervention, and 20 weeks later at follow-up the Hamilton Rating Scale for Depression (HRSD-24) was conducted. In addition, participants completed the Beck Depression Inventory (BDI-II), the Work Ability Index (WAI), the Return to Work Attitude (RTW-SE), and the Insomnia Severity Index (ISI). Results: Symptoms of depression in experts’ as well as in self-rated ratings decreased over time, but more so in the W-IPT condition, compared to the TAU condition (experts rating: large effect size (d = 1.25) and self-assessment; large effect sizes (d = 0.94). The subjective ability to work (WAI) (medium effect size (d = 0.68), self-efficacy to returning to work RTW-SE (medium effect sizes) (d = 0.57) and subjective symptoms of insomnia (ISI) (large effect size) (d = 1.15) increased over time, but again more so in the W-IPT condition, compared to the TAU condition. The effects of the intervention remained stable from the end of the intervention to follow-up. Conclusions: The pattern of results of this pilot study suggests that a newly established fifth IPT focus on workplace-related stress appeared to be particularly efficient in individuals with MDD due to work-related stress in reducing depressive symptoms and reducing sleep complaints as well as in improving occupational outcomes.